The Effect of Health Promotion on Self-Care Behavior of Hypertensive Patients Receiving Services at The Cardiovascular Department in Mahosot Hospital - ສີຫາລາດ, ທ້າວ ອື່ງຄຳ; KHAMKEO , Khonesavanh; SISOULATH , Anousone; PHIMMASONE , Souphaphone; KEOMANY , Vone; SOUNDALA , Oulayvanh; SIKHOTCHOUNLAMANY , Souphavalath (Souphanouvong University Journal Multidisciplinary Research and Development, 2026)
This research is quasi-experimental and aims to study the effects of a health promotion program on self-care behaviors with hypertension who came to service at the Cardiovascular Department of Mahosot Hospital. The samples comprised 16 hypertension patients. The study was conducted over a period of 8 weeks with intervention and follow-up. Interview data were collected by questionnaires in two sets: 1) Data collection tools and 2) Experimental tools. The health promotion program consists of four types of activities: 1) Teaching, 2) Demonstration, 3) Learning exchange from role models, and 4) Telephone prompts. The content was validated by 03 qualified people; the Content Validity Index (CVI) was 0.95. Analyze data using descriptive statistics, including mean and standard deviation. The results found that Overall self-care behaviors of hypertensive patients before the experiment were statistically significant (p-value < 0.001); Systolic blood pressure levels after the experiment were significantly lower than before the experiment (p-value < 0.001), and diastolic blood pressure levels were not significant (p-value < 0.001).These findings suggest that the hypertensive patients in the experimental group were exposed to a health promotion program, which led to better adjustments in self-care behaviors and resulted in decreased hypertension.